Porous silicon-based negative electrode material and preparation method, negative electrode sheet, solid-state battery
By using porous silicon-based anode material in sulfide all-solid lithium batteries and using a combination of silicon-doped ionic conductors and fillers, the interface contact failure caused by strain during the lithiation/delithiation of silicon anode materials is solved, and efficient lithium ion/electronic transmission and battery performance are achieved.
Patent Information
- Application Number
- CN202411930535.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-04-01
AI Technical Summary
The mechanical strain generated by the silicon negative electrode material during the lithiation/delithiation process leads to the solid-solid contact failure of the sulfide all-solid lithium battery interface, limiting the lithium ion/electron transmission environment and affecting the capacity of the silicon negative electrode.
By constructing a porous silicon-based negative electrode material, silicon-doped ion conductors are used as interface layers, and ion conductors and electronic conductors are used as fillers to be located between the inner surface, outer surface of the porous silicon matrix and adjacent silicon skeletons, forming Li-Si-O bonds and/or Li-M-Si-O bonds to improve the lithium ion transmission efficiency of the solid interface.
The high structural stability and high lithium ion/electronic transmission efficiency of porous silicon-based anode materials are achieved, and the coulomb efficiency, rate performance, cycle stability and safety of the battery are improved.
Smart Images

Figure CN119742360A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium-ion batteries, and in particular to a porous silicon-based negative electrode material, a method for preparing the porous silicon-based negative electrode material, a negative electrode plate, and a solid-state battery. Background Art
[0002] All-solid-state lithium-ion batteries have attracted widespread attention due to their high energy density, long cycle life and high safety. Among the many all-solid-state lithium-ion batteries, sulfide all-solid-state batteries are considered to be one of the most promising all-solid-state batteries due to their ultra-high ionic conductivity. In order to meet the design requirements of high-energy-density sulfide all-solid-state batteries, the application of silicon-based negative electrodes to sulfide all-solid-state lithium batteries has become a research hotspot in the industry in recent years.
[0003] Silicon anode is regarded as one of the ideal anode materials for all-solid-state batteries due to its excellent characteristics such as high capacity, low lithium insertion potential, and abundant resources, and has great application potential. However, when applying silicon anode materials to sulfide all-solid-state batteries, the following problems are still faced: 1) During the lithiation / delithiation process, the silicon anode undergoes significant and anisotropic periodic strain evolution, which often leads to the loss of solid-solid contact at the interface of sulfide solid-state lithium batteries, weakening the ion / electron transmission environment and limiting the capacity of the silicon anode; 2) The chemical and electrochemical stability of the interface between silicon anode materials and sulfide solid electrolytes is poor, and there are many side reactions, which will cause both to fail together. Therefore, the mechanical stability and electrochemistry between the silicon anode and the sulfide solid electrolyte pose a huge challenge in realizing stable silicon-based sulfide all-solid-state batteries.
[0004] CN117727889A discloses a stress-adaptive silicon-based composite material, the main preparation process of which is: placing pure silicon negative electrode material, sulfide solid electrolyte, and conductive additive in a mechanical fusion machine according to a certain mass ratio, and then stirring at a certain speed to obtain a silicon-based negative electrode material with a surface coated with sulfide solid electrolyte and conductive additive. Although the electron / ion transmission performance of silicon negative electrode materials has been improved to a certain extent, there are still the following disadvantages: 1) physical mixing is difficult to ensure coating uniformity; 2) it cannot adapt to the huge stress released when silicon is embedded with lithium, and the coating layer will produce irreversible structural damage; 3) the introduction of amorphous carbon as an electronic additive promotes the decomposition of sulfide solid electrolyte, which seriously destroys the crystal structure of sulfide electrolyte and has an adverse effect on the cycle stability of silicon negative electrode.
[0005] CN116154122A discloses a method for preparing a sulfide solid electrolyte coated porous silicon negative electrode material, wherein porous nano silicon and sulfide solid electrolyte are dispersed in a n-butyl ether solvent according to a certain mass ratio, stirred at room temperature for a certain period of time, and then the solvent is removed by a suction filtration method, and finally dried at 100°C. After the mixture is dried, a sulfide solid electrolyte coated porous silicon negative electrode material is obtained. Although the anisotropic expansion problem of silicon during lithiation / delithiation is alleviated to a certain extent, the disadvantages are: 1) the ionic conductivity of the sulfide solid electrolyte that has not undergone secondary heat treatment is low; 2) there is only physical contact between silicon and the sulfide electrolyte, and there is still a large lithium ion migration energy barrier; 3) the surface is coated, and the ion transmission path between the skeleton and the skeleton inside the porous silicon particle still needs to be transmitted along the silicon surface, the transmission path is tortuous, and the rate performance is poor; 4) the sulfide solid electrolyte is only coated on the inner / outer surface of the porous silicon, and the pore structure is not filled with the sulfide solid electrolyte, and the mechanical strength is reduced. Summary of the invention
[0006] The purpose of the present invention is to overcome the problems of uneven / unstable coating of existing silicon negative electrodes, which leads to the inability to have both high structural stability and high ion / electron transmission efficiency, thereby affecting electrochemistry. The present invention provides a porous silicon-based negative electrode material, a method for preparing a porous silicon-based negative electrode material, a negative electrode plate, and a solid-state battery. The porous silicon-based negative electrode material not only has high structural stability, but also has high lithium ion / electron transmission efficiency, effectively improves the solid-solid interface contact, and thus improves the coulombic efficiency, rate performance, cycle stability and safety of the battery.
[0007] In order to achieve the above-mentioned object, the first aspect of the present invention provides a porous silicon-based negative electrode material, the porous silicon-based negative electrode material comprising: a porous silicon substrate, an interface layer and a filler; the filler is an ion conductor and an electronic conductor;
[0008] Wherein, the interface layer is a silicon-doped ion conductor generated by in-situ reaction of silicon oxide and lithium salt on the surface of the porous silicon substrate in an inert atmosphere;
[0009] Wherein, the filler is located in the porous silicon matrix, on the inner surface and / or outer surface of the silicon skeleton, and between adjacent silicon skeletons.
[0010] In the present invention, unless otherwise specified, the interface layer is located on the surface of the porous silicon substrate, and the filler is located in the porous silicon substrate, on the inner and / or outer surface of the silicon skeleton, and between adjacent silicon skeletons.
[0011] The schematic diagram of the cross-sectional structure of the porous silicon-based negative electrode material provided by the present invention is as follows Figure 1As shown, the porous silicon-based negative electrode material includes: a porous silicon substrate, an interface layer and a filler, wherein the interface layer is located on the surface of the porous silicon substrate, and the filler is located between adjacent silicon skeletons of the porous silicon substrate.
[0012] The inventors of the present invention have found that in solid-state batteries, especially sulfide all-solid-state batteries, the key reason that limits the performance of silicon negative electrodes is that the silicon negative electrode generates huge mechanical stress during the cycle, resulting in failure of the silicon-sulfide solid electrolyte interface contact and obstruction of lithium ion / electron transmission. In this regard, building a stable ion and electron transmission path is a prerequisite for promoting the long-term cycle stability of silicon-based negative electrode materials for sulfide all-solid-state batteries under practical conditions.
[0013] To this end, the present invention not only focuses on improving the lithium ion transmission efficiency between solid-solid interfaces, but also pays attention to the stress distribution at the interface. Through reasonable surface interface / bulk structure design, not only the risk of interface contact failure is reduced, but also the lithium ion / electron transmission efficiency is improved, thereby achieving the cycle stability and safety of the battery.
[0014] Specifically, the surface interface structure design refers to the construction of a stable interface layer, in which the silicon oxide on the surface of the porous silicon substrate and the lithium salt react in situ in an inert atmosphere to generate a silicon-doped ion conductor, which not only achieves uniform coating and reduces the energy barrier for lithium ion transmission, but also achieves stable connection with the porous silicon substrate, constructs Li-Si-O bonds and / or Li-M-Si-O bonds, and provides a high-speed transmission channel for lithium ions; the bulk structure design refers to the use of ion conductors and electronic conductors as fillers, especially on the inner surface, outer surface and between adjacent silicon skeletons in the porous silicon matrix, which can not only increase the contact area between the active material and the solid electrolyte and shorten the lithium ion transmission path, but also serve as a stress buffer layer to ensure uniform stress distribution and reduce the risk of interface rupture under high stress conditions, thereby improving the cycle stability and safety of the battery.
[0015] A second aspect of the present invention provides a method for preparing a porous silicon-based negative electrode material, the preparation method comprising:
[0016] (1) mixing a porous silicon substrate, a lithium salt and a solvent, performing a first drying, and then performing a first heat treatment in an inert atmosphere to obtain an interface layer-modified porous silicon substrate as an intermediate;
[0017] (2) After the intermediate is subjected to vacuum treatment, it is mixed with a solution containing an ion conductor and an electron conductor under vacuum conditions for degassing and second drying, and then subjected to a second heat treatment in an inert atmosphere to obtain a porous silicon-based negative electrode material.
[0018] A third aspect of the present invention provides a negative electrode plate, which contains the porous silicon-based negative electrode material provided by the first aspect, or the porous silicon-based negative electrode material prepared by the preparation method provided by the second aspect.
[0019] The fourth aspect of the present invention provides a solid-state battery, which contains the porous silicon-based negative electrode material provided by the first aspect, or the porous silicon-based negative electrode material prepared by the preparation method provided by the second aspect, or the negative electrode plate provided by the third aspect.
[0020] Compared with the prior art, the present invention has the following advantages:
[0021] (1) The porous silicon-based negative electrode material provided by the present invention adopts a specific silicon-doped ion conductor as the interface layer, which not only has uniform coating, but also realizes stable connection with the porous silicon matrix, especially by specific chemical bond connection, thereby improving solid-solid interface ion transmission; at the same time, ion conductors and electron conductors are used as fillers, so that they are located in the porous silicon matrix, the inner surface and / or outer surface of the silicon skeleton, and between adjacent silicon skeletons. In particular, the fillers are located between adjacent silicon skeletons, which can significantly shorten the lithium ion and electron transmission path, improve the lithium ion and electron transmission efficiency, and also enhance the overall mechanical strength of the material, thereby avoiding structural loss caused by external pressure;
[0022] (2) The porous silicon-based negative electrode material provided by the present invention, combined with a specific porous silicon matrix, causes the silicon to expand inward under external pressure, thereby reducing electrode expansion; the filler also has a certain buffering effect, avoiding stress concentration and cracking; in addition, the remaining pores in the porous silicon matrix further alleviate volume expansion;
[0023] (3) The preparation method provided by the present invention first adopts a first heat treatment to make the silicon oxide on the surface of the porous silicon substrate react with the lithium salt in situ to generate a silicon-doped ion conductor as an interface layer, which is connected to the substrate in the form of a chemical bond; then a vacuum treatment and a second heat treatment are adopted to in situ fill the ion conductor and the electron conductor, thereby improving the lithium ion and electron transmission rate, enhancing the mechanical strength, avoiding structural loss, and obtaining a porous silicon-based negative electrode material with a stable structure; in addition, the preparation method also simplifies the process flow and is convenient for industrial production;
[0024] (4) The porous silicon-based negative electrode material provided by the present invention is used in solid-state batteries, especially sulfide solid-state batteries, which have high electrochemical properties, especially coulombic efficiency, rate performance and cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 A schematic diagram of the cross-sectional structure of the porous silicon-based negative electrode material provided by the present invention;
[0026] Figure 2is a SEM image of the porous silicon-based negative electrode material S1 prepared in Example 1;
[0027] Figure 3 is the infrared spectrum of the porous silicon-based negative electrode material S1 prepared in Example 1;
[0028] Figure 4 This is the XRD spectrum of the porous silicon-based negative electrode material S1 prepared in Example 1. DETAILED DESCRIPTION
[0029] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0030] In the present invention, unless otherwise specified, "first" and "second" do not indicate a sequence or limit the materials or steps, but are only used to distinguish or indicate that they are not the same material or step. For example, "first heat treatment" and "second heat treatment" are only used to indicate that they are not the same heat treatment.
[0031] The first aspect of the present invention provides a porous silicon-based negative electrode material, the porous silicon-based negative electrode material comprising: a porous silicon substrate, an interface layer and a filler; the filler is an ion conductor and an electronic conductor;
[0032] Wherein, the interface layer is a silicon-doped ion conductor generated by in-situ reaction of silicon oxide and lithium salt on the surface of the porous silicon substrate in an inert atmosphere;
[0033] Wherein, the filler is located in the porous silicon matrix, on the inner surface and / or outer surface of the silicon skeleton, and between adjacent silicon skeletons.
[0034] In the present invention, unless otherwise specified, the porous silicon substrate is referred to as the substrate.
[0035] In the present invention, the porous silicon substrate not only has a pore structure, but also uses silicon as the main negative electrode active material. Preferably, the porous silicon substrate is selected from porous silicon and / or porous silicon alloy.
[0036] In the present invention, the porous silicon alloy includes but is not limited to aluminum silicon alloy, silicon titanium alloy, silicon iron alloy, silicon copper alloy and the like.
[0037] In some embodiments of the present invention, preferably, in the porous silicon matrix, the radial dimension of the silicon skeleton is 10-500nm, for example, 10nm, 20nm, 30nm, 50nm, 60nm, 80nm, 90nm, 100nm, 200nm, 250nm, 300nm, 400nm, 500nm, and any value in the range between any two values, preferably 10-100nm.
[0038] In the present invention, the radial dimension parameter refers to the length dimension in the diameter direction of the pores formed between silicon skeletons (ie, between adjacent silicon skeletons), which is measured by a scanning electron microscope.
[0039] In some embodiments of the present invention, preferably, the porosity of the porous silicon substrate is 20-80%, for example, 20%, 30%, 35%, 40%, 45%, 50%, 60%, 80%, and any value in the range between any two values, preferably 30-50%.
[0040] In the present invention, the porosity parameter is measured by mercury intrusion method.
[0041] In the present invention, the porous silicon substrate that meets the above radial dimensions and porosity can not only maintain structural stability under external pressure, but also reserve space for the expansion of the pole piece, alleviate volume expansion, and thus improve the cycle performance of the battery.
[0042] In some embodiments of the present invention, preferably, the band gap width of the porous silicon substrate is ≤1.1eV, for example, 1.1eV, 1eV, 0.9eV, 0.85eV, 0.8eV, 0.75eV, 0.7eV, 0.65eV, 0.6eV, 0.5eV, 0.4eV, and any value in the range composed of any two numerical values, preferably 0.6-0.9eV.
[0043] In the present invention, the above-mentioned bandgap width parameter refers to the minimum energy required for the valence electrons of the porous silicon substrate to transition to the conduction band, which can be measured by using an ultraviolet-visible spectrophotometer.
[0044] In the present invention, the silicon-doped ion conductor is prepared by in-situ reaction of silicon oxide on the surface of a porous silicon substrate and a lithium salt in an inert atmosphere, wherein the general formula of silicon oxide is SiO α , 1<α<2. In other words, the porous silicon substrate and the interface layer are connected in the form of chemical bonds, thereby improving the interface lithium ion transmission rate and transmission stability.
[0045] In some embodiments of the present invention, preferably, the interface layer is a silicon-doped ion conductor containing Li-Si-O bonds and / or Li-M-Si-O bonds, wherein M is selected from at least one of Mg, Al, Ti, P, S, B, Sr, Zr, Ca and La. In the present invention, the Li-Si-O bonds and / or Li-M-Si-O bonds are illustrated by infrared spectra and XRD spectra.
[0046] In the present invention, unless otherwise specified, in the Li-M-Si-O bond and / or Li-Si-O bond, Si is derived from silicon oxide on the surface of the porous silicon substrate, Li and M are both derived from lithium salts, and O is derived from silicon oxide and / or lithium salts on the surface of the porous silicon substrate.
[0047] In some embodiments of the present invention, further preferably, the silicon-doped ion conductor is selected from at least one of lithium silicate, lithium titanium silicate, lithium phosphosilicate, lithium sulfur silicate, lithium magnesium silicate, lithium phosphosilicate titanate, lithium borosilicate, lithium strontium silicate, lithium zirconium silicate, lithium calcium silicate and lithium lanthanum silicate.
[0048] In some embodiments of the present invention, preferably, the lithium salt is a salt containing Li and / or a salt containing Li and M, wherein M is selected from at least one of Mg, Al, Ti, P, S, B, Sr, Zr, Ca and La.
[0049] In the present invention, unless otherwise specified, the lithium salt may be a salt containing Li, a salt containing Li and M, or a mixed lithium salt of a salt containing Li and a salt containing Li and M.
[0050] In some embodiments of the present invention, further preferably, the lithium salt is selected from at least one of lithium oxide, lithium carbonate, lithium hydroxide, lithium titanate, lithium phosphate, lithium sulfate, lithium aluminum titanium phosphate, lithium tetrafluoroborate, lithium strontium oxide, lithium zirconate and lithium lanthanate.
[0051] In the present invention, when the lithium salt is a salt containing Li, the interface layer is a silicon-doped ion conductor containing Li-Si-O bonds; or, when the lithium salt is a salt containing Li and M, the interface layer is a silicon-doped ion conductor containing Li-M-Si-O bonds; or, when the lithium salt is a salt containing both Li and Li and M, the interface layer is a silicon-doped ion conductor containing Li-Si-O bonds and Li-M-Si-O bonds.
[0052] In some specific embodiments of the present invention, when the lithium salt is selected from lithium oxide / lithium carbonate / lithium hydroxide, the silicon-doped ion conductor is selected from lithium silicate; when the lithium salt is selected from lithium titanate, the silicon-doped ion conductor is selected from lithium titanium silicate; when the lithium salt is selected from lithium phosphate, the silicon-doped ion conductor is selected from lithium phosphosilicate; when the lithium salt is selected from lithium sulfate, the silicon-doped ion conductor is selected from lithium sulfur silicate; when the lithium salt is selected from lithium aluminum titanium phosphate, the silicon-doped ion conductor is selected from lithium phosphosilicate; when the lithium salt is selected from lithium tetrafluoroborate, the silicon-doped ion conductor is selected from lithium borosilicate; when the lithium salt is selected from lithium strontium oxide, the silicon-doped ion conductor is selected from lithium strontium silicate; when the lithium salt is selected from lithium zirconate, the silicon-doped ion conductor is selected from lithium zirconate; when the lithium salt is selected from lithium lanthanate, the silicon-doped ion conductor is selected from lithium lanthanum silicate.
[0053] In some embodiments of the present invention, preferably, in the filler, the mass ratio of the ion conductor to the electron conductor is (2-9.5):(0.5-8), for example, 2:8, 3:7, 4:6, 5:5, 6:4, 7:3, 8:2, 9:1, 9.5:0.5, and any value in the range consisting of any two values, preferably (5-8):(2-5).
[0054] In the present invention, when the mass ratio of ion conductor to electron conductor is less than 2:8 or higher than 9.5:0.5, only a single conductivity can be guaranteed to be improved, and both ion conductivity and electron conductivity cannot be taken into account at the same time; however, the negative electrode material of the solid-state battery requires not only high ion conductivity, but also high electron conductivity. Therefore, the filler that meets the above mass ratio is conducive to improving the ion and electron transmission rate, thereby improving the ion conductivity and electron conductivity of the porous silicon negative electrode material.
[0055] In some embodiments of the present invention, preferably, the filler is located between adjacent silicon skeletons. In this way, the filler acts as a bridge for the linear transmission of lithium ions and electrons, which can shorten the transmission path of lithium ions and electrons.
[0056] In some embodiments of the present invention, preferably, the D 50 Each independently is 20-500 nm, for example, 20 nm, 50 nm, 80 nm, 100 nm, 150 nm, 200 nm, 250 nm, 300 nm, 400 nm, 500 nm, and any value in a range consisting of any two values, preferably 50-300 nm.
[0057] In the present invention, the D of the ion conductor and the electron conductor 50 It can be the same or different.
[0058] In the present invention, the ion conductor has not only high ionic conductivity but also high Young's modulus. Preferably, the ionic conductivity of the ion conductor is ≥10-11 S / cm; Young's modulus ≥8GPa.
[0059] In the present invention, the ionic conductivity parameter is measured by an AC impedance method, including: sandwiching the sample to be tested between two stainless steel disk electrodes (SS), measuring the ionic conductivity (σ) by electrochemical impedance spectroscopy (EIS), and calculating according to formula (1): Among them, R b is the volume resistance of the sample to be tested (R b Determined by impedance spectrum), L and S are the thickness and area of the sample to be tested.
[0060] In the present invention, the Young's modulus parameter is measured by a tensile measurement method.
[0061] In the present invention, the type of the ion conductor has a wide selection range, as long as it meets the above definition. Preferably, the ion conductor is selected from at least one of lithium phosphate, lithium carbonate, lithium titanate, lithium aluminum titanium phosphate and argyrodite-type electrolyte.
[0062] In some embodiments of the present invention, further preferably, the ion conductor is a sulfide electrolyte, preferably selected from zLi 2 S·(100-z)P 2 S 5 , Li 3 PS 4 , Li 7 P 3 S 11 , Li 6 PS 5 X x , Li 10 M'P 2 S 12 , Li 3.25 Ge 0.25 P 0.75 S 4 , Li 4 G JZ 4 , Li 11 Sn 2 PS 12 and Li 9.54 Si 1.74 P 1.44 S 11.7 Cl 0.3 At least one of the following, wherein 0≤z≤100, X is Cl, Br or I, 1≤x≤1.6, and M' is Ge and / or Sn.
[0063] In some embodiments of the present invention, preferably, the electronic conductivity of the electronic conductor is ≥10 -2 S / cm.
[0064] In the present invention, the electronic conductivity parameter is measured by a powder resistance meter.
[0065] In the present invention, the type of the electronic conductor has a wide selection range, as long as it meets the above definition. Preferably, the electronic conductor is selected from conductive carbon materials and / or nanometals, preferably selected from at least one of single-walled carbon nanotubes (SWCNTs), multi-walled carbon nanotubes (MWCNTs), conductive carbon black, nanocopper and nanosilver, more preferably SWCNTs and / or MWCNTs.
[0066] In some embodiments of the present invention, preferably, the thickness of the interface layer is 1-5 nm, for example, 1 nm, 2 nm, 3 nm, 4 nm, 5 nm, and any value in the range consisting of any two values, preferably 2-3 nm.
[0067] In the present invention, the thickness parameter is measured by SEM.
[0068] In the present invention, if the interface layer is too thin, the interface layer is unstable, and chemical failure (i.e., breakage or detachment) of the interface layer occurs during the expansion / contraction process of the material, and the interface layer fails to connect the matrix and reduce the energy barrier of ion interface transmission. If the interface layer is too thick, the transmission distance of lithium ions from the filler to the matrix will increase, affecting the transmission rate of lithium ions.
[0069] In some embodiments of the present invention, preferably, based on the total mass of the porous silicon-based negative electrode material, the content of the porous silicon matrix is 50-95wt%, for example, 50wt%, 60wt%, 62wt%, 65wt%, 68wt%, 70wt%, 72wt%, 75wt%, 78wt%, 80wt%, 82wt%, 85wt%, 88wt%, 90wt%, 95wt%, and any value in the range composed of any two values, preferably 60-90wt%.
[0070] In some embodiments of the present invention, preferably, based on the total mass of the porous silicon-based negative electrode material, the content of the interface layer is 0.5-5wt%, for example, 0.5wt%, 1wt%, 2wt%, 2.2wt%, 2.5wt%, 2.8wt%, 3wt%, 3.2wt%, 3.5wt%, 3.8wt%, 4wt%, 5wt%, and any value in the range composed of any two values, preferably 2-4wt%.
[0071] In some embodiments of the present invention, preferably, based on the total mass of the porous silicon-based negative electrode material, the content of the filler is 4.5-45wt%, for example, 4.5wt%, 8wt%, 10wt%, 12wt%, 15wt%, 18wt%, 20wt%, 30wt%, 32wt%, 34.5wt%, 36wt%, 40wt%, 45wt%, and any value in the range composed of any two values, preferably 8-36wt%.
[0072] In the present invention, if the content of the filler is too low, the pores are not fully filled, the porosity is high, and the effective contact area with the sulfide electrolyte is reduced, the interface impedance is increased, and it is not conducive to the performance of the material; if the content of the filler is too high, the space reserved for material expansion is reduced, and the material expansion rate is increased. Only when the protection scope defined by the present invention is met, the effective contact area and expansion rate of the material and the solid electrolyte can be taken into account, so that the material performance can be optimized.
[0073] In the present invention, unless otherwise specified, the total content of the porous silicon substrate, the interface layer and the filler is 100 wt %.
[0074] In some embodiments of the present invention, preferably, the ionic conductivity of the porous silicon-based negative electrode material is ≥10 -11 S / cm, for example, 10 -11 S / cm, 1×10 -10 S / cm, 5×10 -10 S / cm, 10 -9 S / cm, 2×10 -9 S / cm, 5×10 -9 S / cm, 8×10 -9 S / cm, 1×10 -8 S / cm, 2×10 -8 S / cm, 5×10 -8 S / cm, 8×10 -8 S / cm, 1×10 -7 S / cm, and any value in the range of any two values, preferably 10 -9 -10 -7 S / cm.
[0075] In some embodiments of the present invention, preferably, the electronic conductivity of the porous silicon-based negative electrode material is ≥0.001S / cm, for example, 0.001S / cm, 0.002S / cm, 0.003S / cm, 0.004S / cm, 0.005S / cm, 0.006S / cm, 0.007S / cm, 0.008S / cm, 0.009S / cm, 0.01S / cm, 0.02S / cm, 0.05S / cm, 0.08S / cm, 0.1S / cm, and any value in the range composed of any two values, preferably 0.001-0.1S / cm.
[0076] In some embodiments of the present invention, preferably, the Li + Diffusion coefficient ≥10 -13 cm 2 / s, for example, 10 -13 cm 2 / s, 2×10 -13 cm 2 / s, 5×10 -13 cm 2 / s, 8×10 -13 cm 2 / s, 1×10 -12 cm 2 / s, 2×10 -12 cm 2 / s, 5×10 -12 cm 2 / s, 8×10 -12 cm 2 / s, 1×10 -11 cm 2 / s, 2×10 -11 cm 2 / s, 5×10 -11 cm 2 / s, 8×10 -11 cm 2 / s, 1×10 -10 cm 2 / s, 2×10 -10 cm 2 / s, 5×10 -10 cm 2 / s, 8×10 -10 cm 2 / s, 1×10 -9 cm 2 / s, and any value in the range of any two values, preferably 10 -13 -10 -9 cm 2 / s.
[0077] In the present invention, the lithium ion diffusion coefficient parameter is measured by constant current intermittent titration (GITT).
[0078] In the present invention, unless otherwise specified, the ionic conductivity parameters, electronic conductivity parameters and Li + The diffusion coefficient parameters were all measured at room temperature, which refers to 25±2°C.
[0079] In some embodiments of the present invention, preferably, the Young's modulus of the porous silicon-based negative electrode material is ≥6.5 GPa, for example, 6.5 GPa, 6.8 GPa, 7.1 GPa, 7.5 GPa, 8 GPa, 8.5 GPa, 9 GPa, 9.5 GPa, 10 GPa, 10.5 GPa, 11 GPa, 11.5 GPa, 12 GPa, 12.5 GPa, 13.5 GPa, GPa, 14 GPa, 15 GPa, and any value in the range composed of any two values, preferably 8-15 GPa.
[0080] The porous silicon-based negative electrode material provided by the present invention has a short lithium ion transmission path, a high ion / electron transmission rate, and a low expansion rate; at the same time, using it in solid-state batteries can improve the battery coulomb efficiency, and improve the rate performance and cycle performance.
[0081] A second aspect of the present invention provides a method for preparing a porous silicon-based negative electrode material, the preparation method comprising:
[0082] (1) mixing a porous silicon substrate, a lithium salt and a solvent, performing a first drying, and then performing a first heat treatment in an inert atmosphere to obtain an interface layer-modified porous silicon substrate as an intermediate;
[0083] (2) After the intermediate is subjected to vacuum treatment, it is mixed with a solution containing an ion conductor and an electron conductor under vacuum conditions for degassing and second drying, and then subjected to a second heat treatment in an inert atmosphere to obtain a porous silicon-based negative electrode material.
[0084] In the present invention, unless otherwise specified, the porous silicon substrate, lithium salt, ion conductor, electron conductor and interface layer are all in accordance with the above definitions, and the present invention will not be elaborated herein.
[0085] In the present invention, in step (1), the amounts of the porous silicon substrate and the lithium salt satisfy: based on the total mass of the porous silicon-based negative electrode material, the content of the porous silicon substrate is 50-95wt%, preferably 60-90wt%; the content of the interface layer is 0.5-5wt%, preferably 2-4wt%.
[0086] In the present invention, in step (1), the solvent is selected from alcohols, ethers, deionized water, etc. Alcohols include but are not limited to methanol, ethanol, etc.; ethers include but are not limited to methyl ether, ethyl ether, etc.
[0087] In the present invention, in step (1), the mixing conditions are: temperature of 15-40°C, preferably 20-30°C; rotation speed of 100-500 rpm, and time of 1-10 h.
[0088] In the present invention, in step (1), the first drying is to remove the solvent so that the lithium salt is evenly coated on the surface of the porous silicon substrate. Preferably, the conditions of the first drying include: a temperature of 60-120°C, preferably 70-100°C; and a time of 1-24h.
[0089] In the present invention, the inert atmosphere includes but is not limited to nitrogen atmosphere, helium atmosphere, argon atmosphere, neon atmosphere, etc., preferably nitrogen atmosphere.
[0090] In the present invention, in step (1), the first heat treatment allows the lithium salt to react in situ with the silicon oxide on the surface of the porous silicon substrate to generate a silicon-doped ion conductor containing Li-Si-O bonds and / or Li-M-Si-O bonds. Preferably, the conditions of the first heat treatment include: a temperature of 200-1000°C, for example, 200°C, 300°C, 500°C, 600°C, 700°C, 800°C, 900°C, 1000°C, and any value in the range of any two values, preferably 500-900°C.
[0091] In the present invention, it is further preferred that the conditions of the first heat treatment also include: a heating rate of 1-10°C / min, for example, 1°C / min, 2°C / min, 3°C / min, 5°C / min, 8°C / min, 10°C / min, and any value in the range composed of any two numerical values, preferably 1-5°C / min; a time of 1-10h, for example, 1h, 2h, 3h, 4h, 6h, 8h, 10h, and any value in the range composed of any two numerical values, preferably 2-6h.
[0092] In the present invention, the conditions of the above-mentioned first heat treatment, especially the temperature range, are met. By performing the first heat treatment on the porous silicon substrate coated with lithium salt, the lithium salt and the silicon oxide on the surface of the porous silicon substrate are prompted to react in situ to generate a silicon-doped ion conductor, thereby reducing the lithium ion transport energy barrier of the material; at the same time, the porous silicon substrate and the interface layer are connected in the form of chemical bonds, which improves the interface lithium ion transport rate while enhancing the structural stability of the material.
[0093] In the present invention, in step (2), the purpose of the vacuum treatment is to exhaust the impurity gas in the pores of the intermediate and provide sufficient space for the ion conductor and the electronic conductor to fill. Preferably, the conditions of the vacuum treatment include: a temperature of 60-100°C, for example, 60°C, 70°C, 80°C, 90°C, 100°C, and any value in the range of any two values; a time of 1-10h, for example, 1h, 2h, 3h, 4h, 6h, 8h, 10h, and any value in the range of any two values.
[0094] In the present invention, the solution containing ion conductor and electron conductor is prepared by mixing ion conductor, electron conductor and organic solvent, wherein the mixing temperature is 15-40°C, preferably 20-30°C; the rotation speed is 100-500rpm, and the time is 1-10h.
[0095] In the present invention, the organic solvent is selected from at least one of alcohols, ethers and nitriles, preferably at least one of acetonitrile (ACN), tetrahydrofuran (THF), ethanol (EA), ethylenediamine (EDA)-1,2-ethanedithiol (EDT) solution, dimethyl ether (DME), dimethyl carbonate (DMC) and hydrazine, more preferably ethanol.
[0096] In some embodiments of the present invention, preferably, the mass ratio of the ion conductor to the electron conductor is (2-9.5):(0.5-8), for example, 2:8, 3:7, 4:6, 5:5, 6:4, 7:3, 8:2, 9:1, and any value in the range consisting of any two values, preferably (5-8):(2-5).
[0097] In the present invention, the purpose of the mixed degassing is to fill the ion conductor and the electron conductor as fillers in situ in the porous silicon substrate. Preferably, the mixed degassing conditions include: a rotation speed of 100-500 rpm and a time of 1-5 hours.
[0098] In the present invention, the second drying is intended to remove the organic solvent. Preferably, the conditions for the second drying include: a temperature of 60-120°C, preferably 70-100°C; and a time of 1-24 hours.
[0099] In the present invention, the second heat treatment is intended to further improve ionic conductivity. Preferably, the conditions of the second heat treatment include: a temperature of 200-600°C, for example, 200°C, 300°C, 350°C, 400°C, 450°C, 500°C, 600°C, and any value in the range of any two values, preferably 300-500°C; a time of 1-10h, for example, 1h, 2h, 3h, 4h, 6h, 8h, 10h, and any value in the range of any two values, preferably 2-8h.
[0100] The porous silicon-based negative electrode material provided by the present invention can be widely used in the fields of solid-state battery technology, interface engineering technology, and material science. In the field of solid-state battery technology, the porous silicon-based negative electrode material provided by the present invention builds a stable and fast lithium ion / electron transmission channel at the material end, realizing efficient, fast, and stable transmission of lithium ions / electrons; in the field of interface engineering technology, the present invention provides a new surface interface modification method, that is, by in-situ construction of Li-Si-O bonds and / or Li-M-Si-O bonds, to achieve close contact between the porous silicon-based negative electrode material and the electrolyte.
[0101] A third aspect of the present invention provides a negative electrode plate, wherein the negative electrode plate comprises the porous silicon-based negative electrode material provided by the first aspect, or the porous silicon-based negative electrode material prepared by the preparation method provided by the second aspect.
[0102] In the present invention, unless otherwise specified, the negative electrode plate comprises: a negative electrode current collector and a negative electrode coating loaded on the negative electrode current collector.
[0103] In some embodiments of the present invention, preferably, in the negative electrode sheet, the negative electrode coating contains the porous silicon-based negative electrode material and a solid electrolyte.
[0104] In the present invention, the solid electrolyte includes but is not limited to at least one of an oxide electrolyte, a sulfide electrolyte, a halide electrolyte and a polymer electrolyte, preferably a sulfide electrolyte, including but not limited to zLi 2 S·(100-z)P 2 S 5 , Li 3 PS 4 , Li 7 P 3 S 11 , Li 6 PS 5 X x , Li 10 M'P 2 S 12 , Li 3.25 Ge 0.25 P0.75 S 4 , Li 4 G JZ 4 , Li 11 Sn 2 PS 12 and Li 9.54 Si 1.74 P 1.44 S 11.7 Cl 0.3 etc., wherein 0≤z≤100, X is Cl, Br or I, 1≤x≤1.6, and M' is Ge and / or Sn.
[0105] In the present invention, further preferably, the negative electrode coating further contains a conductive agent and a binder.
[0106] In the present invention, the conductive agent is selected from at least one of gas-phase carbon nanotubes, conductive carbon black, carbon fiber, carbon nanotubes, acetylene black, Ketjen black, graphite and graphene; the binder is selected from at least one of polyvinylidene fluoride (PVDF), styrene butadiene rubber (SBR), carboxymethyl cellulose (CMC), polytetrafluoroethylene (PTFE), nitrile rubber (NBR), polyacrylonitrile (PAN), polyacrylic acid (PAA) and polyacrylate. In the present invention, polyacrylate includes but is not limited to polymethyl acrylate, polyethyl acrylate and polypropyl acrylate.
[0107] In some embodiments of the present invention, preferably, in the negative electrode coating, the mass ratio of the porous silicon-based negative electrode material, the solid electrolyte, the conductive agent and the binder is 60-95:40-5:0-5:0-5, preferably 60-94:30-5:0.5-5:0.5-5.
[0108] In some embodiments of the present invention, preferably, the volume expansion rate of the negative electrode plate is ≤70%, for example, 70%, 60%, 50%, 47%, 45%, 40%, 35%, 30%, 25%, 20%, and any value in the range of any two values, preferably 20-50%.
[0109] In the present invention, the volume expansion rate parameter is measured by the following method: the coated electrode (the content of porous silicon-based negative electrode material is 70wt%) is measured for thickness L1 by a spiral positioner before the battery is installed, and then the battery after the first cycle of lithiation is disassembled from the battery mold, and the positive electrode and electrolyte are peeled off with a scraper to obtain the negative electrode electrode, and the thickness of the negative electrode layer L2 is measured by a spiral positioner. The volume expansion rate of the electrode is calculated to be (L2-L1) / L1×100.
[0110] In some embodiments of the present invention, preferably, the negative electrode sheet is prepared by the following method: the porous silicon-based negative electrode material, solid electrolyte, conductive agent, binder and organic solvent are mixed in proportion to obtain slurry; the slurry is coated on the negative electrode current collector and dried to obtain the negative electrode sheet. In the present invention, the drying temperature is 75-90°C.
[0111] The fourth aspect of the present invention provides a solid-state battery, which contains the porous silicon-based negative electrode material provided by the first aspect, or the porous silicon-based negative electrode material prepared by the preparation method provided by the second aspect, or the negative electrode plate provided by the third aspect.
[0112] In the present invention, the solid-state battery further comprises: a positive electrode plate and a solid electrolyte. In the present invention, unless otherwise specified, the solid electrolyte is based on the above definition, and the present invention will not be elaborated herein.
[0113] The present invention will be described in detail below through examples.
[0114] Porous silicon material P1, radial size is 80nm, porosity is 40%, and bandgap is 1.08eV;
[0115] Porous silicon material P2, with a radial dimension of 300 nm, a porosity of 30%, and a bandgap of 1.08 eV;
[0116] The porous silicon material P3 has a radial dimension of 30 nm, a porosity of 50%, and a bandgap of 1.08 eV.
[0117] Example 1
[0118] (1) 0.4 g of lithium phosphate (D 50 The ionic conductivity is 10 at 25℃. -9 S / cm, Young's modulus is 80GPa) is dispersed in 200mL deionized water, and stirred continuously for 0.5h, 20g of porous silicon material P1 is added, and stirred and dispersed continuously at a speed of 300rpm for 5h; the deionized water is removed by suction filtration, and the filter cake is placed in a constant temperature oven at 80℃ and dried for 12h; the precursor obtained after drying is transferred to a tube furnace, and the temperature is increased to 700℃ at a heating rate of 3℃ / min, and the first heat treatment is carried out in an argon atmosphere for 4h to obtain a porous silicon material P1 modified with a lithium phosphosilicate interface layer as an intermediate;
[0119] (2) In a drying room (dew point below 50°C), weigh 3.76 g of Li 6 PS 5 Cl electrolyte powder (D 50 The diameter is 150nm, and the ionic conductivity is 10 at 25℃ -3S / cm, Young's modulus of 12 GPa) was added to 100 mL of anhydrous ethanol and stirred at 300 rpm for 24 h; 0.94 g of SWCNTs (average length of 20 μm, aspect ratio of 2000, electronic conductivity of 10 at 25 °C) was weighed. 2 S / cm) was added to the above solution, and the stirring and dispersion was continued at 300 rpm for 1 h;
[0120] The intermediate was placed in a vacuum oven and dried at 80°C for 6 hours to obtain a dried intermediate; 10 g of the dried intermediate was added to the mixed solution, and transferred to a vacuum stirrer, and degassed at a speed of 300 rpm for 1 hour; after the degassed solution was completed, the temperature of the vacuum stirrer was adjusted to 80°C, and the solvent was evaporated;
[0121] The completely dried material was transferred to a tube furnace and subjected to a second heat treatment at 450° C. for 5 h in an argon atmosphere to obtain a porous silicon-based negative electrode material S1.
[0122] The SEM image of the porous silicon-based negative electrode material S1 is as follows: Figure 2 As shown, the porous silicon-based negative electrode material S1 includes a porous silicon material P1, an interface layer containing lithium phosphosilicate, and ion conductors and electronic conductors located between the inner surface, outer surface, and skeleton of the porous silicon material P1.
[0123] Among them, the infrared spectrum of the porous silicon-based negative electrode material S1 is as follows Figure 3 As shown, the porous silicon-based negative electrode material S1 has a wave number of 485.97 cm -1 , corresponding to the Li-O bond; the wave number is 865.8 cm -1 and 1106.94cm -1 , corresponding to the Si-O bond; the wave number is 1174.43 cm -1 , corresponding to the P=O bond, and the wave number is 1045.22 cm -1 and 941.09cm -1 At the position corresponding to the PO bond, the above bonds exist simultaneously, indicating that there are Li-P-Si-O bonds in the porous silicon-based negative electrode material S1.
[0124] Among them, the XRD spectrum of the porous silicon-based negative electrode material S1 is as follows Figure 4 As shown, the porous silicon-based negative electrode material S1 generates a Li-P-Si-O phase.
[0125] Example 2
[0126] According to the method of Example 1, the difference is that
[0127] In step (1), 0.4 g of lithium phosphate is replaced with 0.4 g of lithium hydroxide to obtain a porous silicon material P1 modified with a lithium silicate interface layer;
[0128] The other conditions are the same to obtain the porous silicon-based negative electrode material S2.
[0129] Example 3
[0130] According to the method of Example 1, the difference is that
[0131] In step (1), 0.4 g of lithium phosphate is replaced by 0.4 g of lithium titanate (D 50 The ionic conductivity is 10 at 25℃. - 8 S / cm, Young's modulus is 115 GPa), and a porous silicon material P1 modified with a lithium titanium silicate interface layer is obtained;
[0132] The other conditions were the same to obtain the porous silicon-based negative electrode material S3.
[0133] Example 4
[0134] According to the method of Example 1, the difference is that
[0135] In step (1), 0.4 g of lithium phosphate is replaced with 0.1 g of lithium phosphate;
[0136] The other conditions are the same to obtain porous silicon-based negative electrode material S4.
[0137] Example 5
[0138] According to the method of Example 1, the difference is that
[0139] In step (1), 0.4 g of lithium phosphate is replaced with 1.05 g of lithium phosphate;
[0140] The other conditions were the same to obtain the porous silicon-based negative electrode material S5.
[0141] Example 6
[0142] According to the method of Example 1, the difference is that
[0143] In step (2), Li 6 PS 5 Cl was replaced by lithium aluminum titanium phosphate (abbreviated as LATP; D 50 The ionic conductivity is 10 at 25℃. -3 S / cm, Young's modulus is 30GPa);
[0144] The other conditions were the same to obtain the porous silicon-based negative electrode material S6.
[0145] Example 7
[0146] According to the method of Example 1, the difference is that
[0147] In step (2), SWCNTs are replaced by SP(D 50 50nm, electronic conductivity at 25℃ is 0.05S / cm);
[0148] The remaining conditions were the same to obtain the porous silicon-based negative electrode material S7.
[0149] Example 8
[0150] According to the method of Example 1, the difference is that
[0151] In step (2), 3.76 g of Li 6 PS 5 Cl and 0.94 g SWCNTs were replaced by 1.88 g Li 6 PS 5 Cl and 2.82 g of SWCNTs;
[0152] The other conditions were the same to obtain the porous silicon-based negative electrode material S8.
[0153] Example 9
[0154] According to the method of Example 1, the difference is that
[0155] In step (2), 3.76 g of Li 6 PS 5 Cl and 0.94 g SWCNTs were replaced by 4.465 g Li 6 PS 5 Cl and 0.235 g of SWCNTs;
[0156] The other conditions were the same to obtain the porous silicon-based negative electrode material S9.
[0157] Example 10
[0158] According to the method of Example 1, the difference is that
[0159] In step (2), 3.76 g of Li 6 PS 5 Cl is replaced by 0.88 g Li 6 PS 5 Cl, 0.94 g of SWCNTs was replaced by 0.22 g of SWCNTs;
[0160] The other conditions were the same to obtain the porous silicon-based negative electrode material S10.
[0161] Embodiment 11
[0162] According to the method of Example 1, the difference is that
[0163] In step (2), 3.76 g of Li 6 PS 5 Cl is replaced by 5.336 g of Li 6 PS 5 Cl, 0.94 g of SWCNTs were replaced by 1.334 g of SWCNTs;
[0164] The other conditions were the same to obtain the porous silicon-based negative electrode material S11.
[0165] Example 12
[0166] According to the method of Example 1, the difference is that
[0167] In step (2), the temperature of the first heat treatment is replaced with 500° C.;
[0168] The other conditions are the same to obtain the porous silicon-based negative electrode material S12.
[0169] Example 13
[0170] According to the method of Example 1, the difference is that
[0171] In step (2), the temperature of the first heat treatment is replaced with 900° C.;
[0172] The other conditions are the same to obtain the porous silicon-based negative electrode material S13.
[0173] Embodiment 14
[0174] According to the method of Example 1, the difference is that
[0175] In step (1), 20 g of porous silicon material P1 is replaced with 20 g of porous silicon material P2 to obtain porous silicon material P2 modified with a lithium phosphosilicate interface layer as an intermediate;
[0176] The other conditions are the same to obtain porous silicon-based negative electrode material S14.
[0177] Embodiment 15
[0178] According to the method of Example 1, the difference is that
[0179] In step (1), 20 g of porous silicon material P1 is replaced with 20 g of porous silicon material P3 to obtain porous silicon material P3 modified with lithium phosphosilicate interface layer as an intermediate;
[0180] The other conditions are the same to obtain the porous silicon-based negative electrode material S15.
[0181] Comparative Example 1
[0182] 20 g of porous silicon material P1 was directly used as porous silicon-based negative electrode material DS1.
[0183] Comparative Example 2
[0184] The method of Example 1 is followed, except that step (2) is omitted, i.e.,
[0185] The intermediate obtained in step (1) is directly used as the porous silicon-based negative electrode material DS2.
[0186] Comparative Example 3
[0187] The method of Example 1 is followed, except that step (1) is omitted, i.e.,
[0188] In step (2), 10 g of the dried intermediate is replaced with 10 g of porous silicon material P1;
[0189] The other conditions were the same, and the porous silicon-based negative electrode material DS3 was obtained.
[0190] Comparative Example 4
[0191] According to the method of Example 1, the difference is that
[0192] Step (1), replacing 0.4 g of lithium phosphate with 0.4 g of lithium fluoride;
[0193] The other conditions were the same, and the porous silicon-based negative electrode material DS4 was obtained.
[0194] Comparative Example 5
[0195] According to the method of Example 1, the difference is that
[0196] In step (2), 3.76 g of Li 6 PS 5 Cl 1.6 and 0.94 g of SWCNTs were replaced by 0.248 g of Li 6 PS 5 Cl 1.6 and 0.062 g of SWCNTs,
[0197] The other conditions were the same, and the porous silicon-based negative electrode material DS5 was obtained.
[0198] Table 1
[0199]
[0200] Note: 1- The mass ratio of ion conductor and electron conductor in the filler; 2- The mass ratio of porous silicon matrix, interface layer and filler in the porous silicon negative electrode material.
[0201] Table 1
[0202]
[0203]
[0204] It can be seen from the results in Table 1 that compared with Comparative Examples 1-5, Examples 1-15 use the porous silicon-based negative electrode material provided by the present invention, silicon-doped ion conductors containing specific Li-M-Si-O bonds and / or Li-Si-O bonds, and combined with specific fillers, which not only have high ionic conductivity, high electronic conductivity and high Li + diffusion coefficient, and also has high mechanical strength and low volume expansion rate, which improves the lithium ion and electron transmission efficiency, as well as structural stability.
[0205] Test Case
[0206] The porous silicon-based negative electrode materials prepared in the above Examples 1-15 and Comparative Examples 1-5 were assembled into sulfide solid-state batteries, and performance tests were performed.
[0207] Preparation of negative electrode sheet: The above-mentioned porous silicon-based negative electrode materials (S1-S15 and DS1-DS5), sulfide solid electrolyte (Li 6 PS 5 Cl), a conductive agent (conductive carbon black SP), and a binder (PVDF) are mixed in a mass ratio of 70:25:2:3, and an appropriate amount of solvent is added to obtain a slurry; the above slurry is coated on a copper foil and dried at 80°C to obtain solid electrodes.
[0208] Assembling sulfide solid-state batteries: Using the above solid-state electrode as the positive electrode, sulfide Li 6 PS 5 Cl is the middle electrolyte layer and lithium indium alloy is the negative electrode. The solid-state battery capacity and cycle performance are tested, and the test results are listed in Table 2.
[0209] Table 2
[0210]
[0211] It can be seen from the data in Table 1-2 that compared with Comparative Examples 1-5, Example 1-15 uses the porous silicon-based negative electrode material provided by the present invention for sulfide solid-state batteries, which not only has high ion / electronic conductivity and high ion diffusion coefficient, but also has high Young's modulus and low volume expansion rate, which can effectively improve the first efficiency, rate performance and cycle stability.
[0212] Compared with Example 1 and Comparative Examples 1-3, it can be seen that when the porous silicon-based negative electrode material does not contain an interface layer and a filler, or only contains an interface layer, or only contains a filler, it is difficult to achieve stable performance. That is, in comparative example 1, when there is neither an interface layer nor a filler, the ion / electronic conductivity of the porous silicon-based negative electrode material is poor, the Young's modulus is low, and the performance of the material itself is difficult to be effectively exerted; when comparative example 2 contains only a single specific interface layer, although the ion conductivity can be improved to a certain extent, the electronic conductivity is not improved, and the Young's modulus is still low; when comparative example 3 contains only a specific filler, although the ion / electronic conductivity is improved to a certain extent, the transmission energy barrier for external lithium ions to reach the matrix is still high; and embodiment 1 contains both a specific interface layer and a specific filler. The specific interface layer can not only reduce the transmission energy barrier of lithium ions to the porous silicon matrix and increase the diffusion coefficient of lithium ions, but also ensure the transmission stability of lithium ions. The filler can improve the Young's modulus of the porous silicon-based negative electrode material while improving the ion / electronic conductivity. Through the synergistic effect of the interface layer and the filler, not only the lithium ion / electron transmission efficiency, conductivity and Li of the porous silicon-based negative electrode material can be effectively improved, but also the transmission efficiency of the porous silicon-based negative electrode material can be effectively improved. + The diffusion coefficient can also optimize the mechanical strength and volume expansion rate of porous silicon-based negative electrode materials, thereby effectively improving the electrochemical performance of the battery.
[0213] It can be seen from Examples 1-3 and Comparative Example 4 that by adjusting the type of interface layer, especially by using silicon-doped ion conductors that form specific Li-M-Si-O bonds and / or Li-Si-O bonds with silicon oxide on the surface of the substrate, the ion / electronic conductivity and structural stability of the porous silicon-based negative electrode material are improved, thereby improving the electrochemical performance of the battery. However, Comparative Example 4 cannot form a specific interface layer on the surface of the substrate, so it can neither achieve the effect of reducing the energy barrier for lithium ion transmission nor ensure the stability of lithium ion transmission.
[0214] It can be seen from Example 1 and Examples 4-5 that by adjusting the thickness of the interface layer, the ionic conductivity and lithium ion diffusion coefficient of the material can be improved, thereby improving the first efficiency, rate performance and cycle stability of the battery.
[0215] It can be seen from Examples 1 and 6-7 that the ionic conductivity, electronic conductivity, Li + diffusion coefficient, mechanical strength and volume expansion rate, thereby improving the battery's first efficiency, rate performance and cycle stability.
[0216] It can be seen from Example 1 and Examples 8-9 that by adjusting the mass ratio of each component in the filler and then adjusting the filling ratio of the ion conductor / electronic conductor, a porous silicon-based negative electrode material with better ionic conductivity / electronic conductivity is obtained.
[0217] It can be seen from Example 1, Examples 10-11 and Comparative Example 5 that when the content of the filler is too low, such as Comparative Example 5, the pores are not fully filled and the porosity is high, which leads to a decrease in the effective contact area between the porous silicon-based negative electrode material and the sulfide electrolyte, an increase in the interface impedance, and a disadvantageous effect on the performance of the material; and when the content of the filler is too high, the space reserved for material expansion is reduced and the material expansion rate increases. By adjusting the mass proportion of the filler, the proportion of the porous silicon matrix, the interface layer, and the filler is adjusted, and a porous silicon-based negative electrode material with better ionic conductivity / electronic conductivity, higher Young's modulus, and lower volume expansion rate is obtained.
[0218] It can be seen from Examples 1 and 12-13 that by regulating the temperature of the first heat treatment, the strength of the Li-M-Si-O bond and / or the Li-Si-O bond is controlled, thereby improving the stability of the interface layer and the ionic conductivity and lithium ion diffusion coefficient of the porous silicon-based negative electrode material.
[0219] It can be seen from Example 1 and Examples 14-15 that by adjusting the type of porous silicon substrate, the pore structure of the porous silicon-based negative electrode material can be adjusted, thereby improving the volume expansion rate of the porous silicon-based negative electrode material.
[0220] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A porous silicon-based negative electrode material, characterized in that: The porous silicon-based negative electrode material comprises: a porous silicon substrate, an interface layer and a filler; the filler is an ion conductor and an electronic conductor; Wherein, the interface layer is a silicon-doped ion conductor generated by in-situ reaction of silicon oxide and lithium salt on the surface of the porous silicon substrate in an inert atmosphere; Wherein, the filler is located in the porous silicon matrix, on the inner surface and / or outer surface of the silicon skeleton, and between adjacent silicon skeletons.
2. The porous silicon-based negative electrode material according to claim 1, wherein: The porous silicon substrate is selected from porous silicon and / or porous silicon alloy; Preferably, in the porous silicon substrate, the radial dimension of the silicon skeleton is 10-500 nm, preferably 10-100 nm; Preferably, the porosity of the porous silicon substrate is 20-80%, preferably 30-50%; Preferably, the band gap of the porous silicon substrate is ≤1.1 eV, preferably 0.6-0.9 eV.
3. The porous silicon-based negative electrode material according to claim 1 or 2, wherein: The interface layer is a silicon-doped ion conductor containing Li-Si-O bonds and / or Li-M-Si-O bonds, wherein M is selected from at least one of Mg, Al, Ti, P, S, B, Sr, Zr, Ca and La.
4. The porous silicon-based negative electrode material according to any one of claims 1 to 3, wherein: The silicon-doped ion conductor is selected from at least one of lithium silicate, lithium titanium silicate, lithium phosphosilicate, lithium sulfur silicate, lithium magnesium silicate, lithium phosphosilicate titanate, lithium borosilicate, lithium strontium silicate, lithium zirconium silicate, lithium calcium silicate and lithium lanthanum silicate; Preferably, the lithium salt is a salt containing Li, and / or a salt containing Li and M, wherein M is selected from at least one of Mg, Al, Ti, P, S, B, Sr, Zr, Ca and La; Further preferably, the lithium salt is selected from at least one of lithium oxide, lithium carbonate, lithium hydroxide, lithium titanate, lithium phosphate, lithium sulfate, lithium aluminum titanium phosphate, lithium tetrafluoroborate, lithium strontium oxide, lithium zirconate and lithium lanthanate.
5. The porous silicon-based negative electrode material according to any one of claims 1 to 4, wherein: In the filler, the mass ratio of the ion conductor to the electron conductor is (2-9.5):(0.5-8), preferably (5-8):(2-5); Preferably, the filler is located between adjacent silicon skeletons; Preferably, the D of the ion conductor and the electron conductor 50 Each independently is 20-500 nm, preferably 50-300 nm.
6. The porous silicon-based negative electrode material according to any one of claims 1 to 5, wherein: The ionic conductivity of the ion conductor is ≥10 -11 S / cm, Young's modulus ≥8GPa; Further preferably, the ion conductor is selected from at least one of lithium phosphate, lithium carbonate, lithium titanate, lithium aluminum titanium phosphate and argyrodite-type electrolyte; More preferably, the ion conductor is a sulfide electrolyte, preferably selected from zLi2S·(100-z)P2S5, Li3PS4, Li7P3S 11 、Li6PS5X x , Li 10 M'P2S 12 , Li 3.25 Ge 0.25 P 0.75 S4, Li4GeS4, Li 11 Sn2PS 12 and Li 9.54 Si 1.74 P 1.44 S 11.7 Cl 0.3 At least one of the following, wherein 0≤z≤100, X is Cl, Br or I, 1≤x≤1.6, and M' is Ge and / or Sn; Preferably, the electronic conductivity of the electronic conductor is ≥10 -2 S / cm; Preferably, the electronic conductor is selected from conductive carbon materials and / or nanometals, preferably at least one selected from single-walled carbon nanotubes, multi-walled carbon nanotubes, conductive carbon black, nanocopper and nanosilver.
7. The porous silicon-based negative electrode material according to any one of claims 1 to 6, wherein: The thickness of the interface layer is 1-5 nm, preferably 2-3 nm; Preferably, based on the total mass of the porous silicon-based negative electrode material, the content of the porous silicon matrix is 50-95wt%, preferably 60-90wt%; the content of the interface layer is 0.5-5wt%, preferably 2-4wt%; the content of the filler is 4.5-45wt%, preferably 8-36wt%.
8. The porous silicon-based negative electrode material according to any one of claims 1 to 7, wherein: The ionic conductivity of the porous silicon-based negative electrode material is ≥10 -11 S / cm, preferably 10 -9 -10 -7 S / cm; Preferably, the electronic conductivity of the porous silicon-based negative electrode material is ≥0.001 S / cm, preferably 0.001-0.1 S / cm; Preferably, the Li of the porous silicon-based negative electrode material + Diffusion coefficient ≥10 -13 cm 2 / s, preferably 10 -13 -10 -9 cm 2 / s; Preferably, the Young's modulus of the porous silicon-based negative electrode material is ≥6.5 GPa, preferably 8-15 GPa.
9. A method for preparing a porous silicon-based negative electrode material, characterized in that: The preparation method comprises: (1) mixing a porous silicon substrate, a lithium salt and a solvent, performing a first drying, and then performing a first heat treatment in an inert atmosphere to obtain an interface layer-modified porous silicon substrate as an intermediate; (2) After the intermediate is subjected to vacuum treatment, it is mixed with a solution containing an ion conductor and an electron conductor under vacuum conditions for degassing and second drying, and then subjected to a second heat treatment in an inert atmosphere to obtain a porous silicon-based negative electrode material.
10. The preparation method according to claim 9, wherein: In step (1), the conditions of the first heat treatment include: a temperature of 200-1000° C., preferably 500-900° C.; Preferably, the conditions of the first heat treatment also include: a heating rate of 1-10°C / min, preferably 1-5°C / min; a time of 1-10h, preferably 2-6h; Preferably, the lithium salt is a salt containing Li, and / or a salt containing Li and M, wherein M is selected from at least one of Mg, Al, Ti, P, S, B, Sr, Zr, Ca and La; Preferably, the interface layer is a silicon-doped ion conductor containing Li-Si-O bonds and / or Li-M-Si-O bonds, wherein M is selected from at least one of Mg, Al, Ti, P, S, B, Sr, Zr, Ca and La; Preferably, in step (2), the vacuum treatment conditions include: temperature of 60-100° C.; time of 1-10 h; Preferably, the conditions of the second heat treatment include: temperature of 200-600°C, preferably 300-500°C; time of 1-10h, preferably 2-8h.
11. A negative electrode plate, characterized in that: The negative electrode plate contains the porous silicon-based negative electrode material according to any one of claims 1 to 8, or the porous silicon-based negative electrode material prepared by the preparation method according to claim 9 or 10; Preferably, in the negative electrode plate, the solid electrolyte is selected from sulfide electrolyte; Preferably, the volume expansion rate of the negative electrode plate is ≤70%, preferably 20-50%.
12. A solid-state battery, characterized in that: The solid-state battery contains the porous silicon-based negative electrode material according to any one of claims 1 to 8, or the porous silicon-based negative electrode material prepared by the preparation method according to claim 9 or 10, or the negative electrode sheet according to claim 11.
Citation Information
Patent Citations
Stress self-adaptive silicon-based composite negative electrode material, preparation method thereof and solid-state battery
CN117727889A